Air Washington : creating careers in aerospace - Kershner, Jim, 1953- (Air Washington in association with HistoryLink, 2015)
"In 2010, unemployment in Washington State hit a Great Recession high of 10.4 percent. Yet the Boeing Company was having trouble finding skilled workers to build its planes, including the revolutionary new 787 Dreamliner. Several of the state's community college president's began looking for ways to address this economic disconnect. One of them, Joe Dunlap of Spokane Community College, found a possible solution in Washington, D.C., where the U.S. Department of Labor was preparing to distribute $2 billion in grants for workforce education and training as part of President Barack Obama's economic stimulus program. They asked for the maximum single grant amount- $20 million- and they got it. Four years after the program started, more than 4,700 students have graduated and moved into the booming aerospace workforce, changing the lives of many for the better. This book recounts how the unusual educational initiative was put together, and what it taught both educators and students."